2023
DOI: 10.7150/jca.81899
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancement of PD-L1 Detection Technologies and Clinical Applications in the Era of Precision Cancer Therapy

Abstract: Programmed death-1 is a protein found on the surface of immune cells that can interact with its ligand, programmed death-ligand 1 (PD-L1), which is expressed on the plasma membrane, the surface of secreted cellular exosomes, in cell nuclei, or as a circulating soluble protein. This interaction can lead to immune escape in cancer patients. In clinical settings, PD-L1 plays an important role in tumor disease diagnosis, determining therapeutic effectiveness, and predicting patient prognosis. PD-L1 inhibitors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…As PDL1+ is a dynamic biomarker whose expression is stimulated in response to IFN gamma by TILs, it can be hypothesized that PDL1+ expression simply reflects a more inflammatory tumor microenvironment. To date, no further insights have been gained from clinical trials [ 107 , 108 ]. For instance, in the Keynote 028 phase 1B multi-cohort study, which involved 24 PDL1+ patients, an ORR of 17% was observed [ 109 ].…”
Section: Role Of the Tumor Immune Microenvironment In Asccmentioning
confidence: 99%
“…As PDL1+ is a dynamic biomarker whose expression is stimulated in response to IFN gamma by TILs, it can be hypothesized that PDL1+ expression simply reflects a more inflammatory tumor microenvironment. To date, no further insights have been gained from clinical trials [ 107 , 108 ]. For instance, in the Keynote 028 phase 1B multi-cohort study, which involved 24 PDL1+ patients, an ORR of 17% was observed [ 109 ].…”
Section: Role Of the Tumor Immune Microenvironment In Asccmentioning
confidence: 99%
“…Several studies have been carried out to show that the efficacy of PD-1/PD-L1 inhibitors is positively correlated with the expression of PD-L1 protein, and different induction modalities are capable to shift the PD-L1 expression on the tumor surface, while radiotherapy is one of the effective modalities to upregulation of PD-L1 [51,52]. Schweiger and collegues have comfirmed that radiotherapy modulated the immune suppression by increasing the PD-L1 expression of macrophages to affect Glioblastoma resistance [53].…”
Section: The Aes Of Pd-1/pd-l1 Inhibitors With Radiotherapymentioning
confidence: 99%
“…However, developing a robust preliminary assay tool that enables in situ monitoring of PD-L1 at the cellular level and offers reliable and quantitative real-time diagnostic results remains a challenge. [13][14][15][16] A variety of sensors have been explored to achieve accurate detection of disease-related biomarkers and meet the increasing demand for point-of-care medical diagnostics. The performance of sensors in terms of reproducibility, robustness, reliability, and accuracy has been the focus of significant research efforts in recent years.…”
Section: Introductionmentioning
confidence: 99%